Single-breath analysis using a novel simple sampler and capillary electrophoresis with contactless conductometric detection - Greguš, Michal; Foret, František; Kubáň, Petr (Electrophoresis, 2015)
The analysis of ionic content of exhaled breath condensate (EBC) from one single breath by CE with C(4) D is demonstrated for the first time. A miniature sampler made from a 2-mL syringe and an aluminum cooling cylinder for collection of EBC was developed. Various parameters of the sampler that influence its collection efficiency, repeatability, and effect of respiratory patterns were studied in detail. Efficient procedures for the cleanup of the miniature sampler were also developed and resulted in significant improvement of sampling repeatability. Analysis of EBC was performed by CE-C(4) D in a 60 mM MES/l-histidine BGE with 30 μM CTAB and 2 mM 18-crown-6 at pH 6 and excellent repeatability of migration times (RSD < 1.3% (n = 7)) and peak areas (RSD < 7% (n = 7)) of 12 inorganic anions, cations, and organic acids was obtained. It has been shown that the breathing pattern has a significant impact on the concentration of the analytes in the collected EBC. As the ventilatory pattern can be easily controlled during single exhalation, the developed collection system and method provides a highly reproducible and fast way of collecting EBC with applicability in point-of-care diagnostics.
Keywords: Equipment Design; konduktometrie; Exhalation; Capillary electrophoresis; Miniaturization; Specimen Handling; Anions; kationty; Electrophoresis, Capillary; elektroforéza kapilární; Cations; Reproducibility of Results; lidé; Breath Tests; Asthma; Conductometry; miniaturizace; reprodukovatelnost výsledků; Single-breath analysis; bronchiální astma; vydechnutí; Exhaled breath condensate; Contactless conductivity detection; dechové testy; anionty; odběr biologického vzorku; design vybavení; Humans